JAMINAN SOSIAL BAGI PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA DAN PEKERJA: STUDI KOMPARASI SERTA MODEL IDEAL - Azani, Adila (Unram Law Review, 2025)
Contract-based Government Employees (PPPK) fall under the scope of employment law, as do private sector workers. Both PPPK and private workers are entitled to rights regulated by law, one of which is the right to social security protection. However, there exists a significant disparity between the social security benefits received by PPPK and those received by private sector workers. The benefits available to private workers are considered more comprehensive, even though both PPPK and workers are employed under fixed-term agreements and are exposed to similar risks, including the potential loss of employment. This paper examines the current state of social security protection for PPPK and private sector workers, as well as the ideal formulation of a social security system specifically for PPPK. Using a juridical-normative approach and descriptive research method, the study reveals that social security coverage for private workers generally includes health insurance, old age security, pension security, work accident security, death security, and job loss security. Meanwhile, PPPK are currently only entitled to health insurance, work accident security, and death security. Based on these findings, the study proposes that the ideal social security framework for PPPK should also encompass old age security, pension security, and job loss security to ensure more equitable and comprehensive protection in line with the nature and risks of their employment status.